Etika Profesi Keguruan dan Profesionalisme Guru - Achmad Fauzi; Ma’mun Hanif; Muhamad A’tho Fiizatillah; Maulana Dziroshofar putra suliwa; Hifni el Musyafa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine teacher professional ethics and its relationship with teacher professionalism through a literature review approach. The method employed in this study was a literature review by collecting and analyzing various scientific sources, including books, journals, and relevant research articles. The findings indicate that teacher professional ethics serve as moral guidelines in regulating teachers' attitudes, behaviors, and responsibilities in carrying out their duties. The teachers' code of ethics provides a foundation for building integrity, maintaining public trust, and fostering harmonious relationships with students, fellow teachers, schools, and the community. Teacher professionalism is reflected in the mastery of pedagogical, professional, personal, and social competencies, as well as the ability to adapt to the advancement of science and technology. Therefore, the consistent implementation of professional ethics and continuous professional development are essential factors in improving the quality of learning and educational outcomes.